2017
DOI: 10.3127/ajis.v21i0.1454
|View full text |Cite
|
Sign up to set email alerts
|

Predicting User Acceptance and Continuance Behaviour Towards Location-based Services: The Moderating Effect of Facilitating Conditions on Behavioural Intention and Actual Use

Abstract: The purpose of this study is to establish and examine the significance of a consumer acceptance and continuance model for location-based services (LBSs) through the integration of perceived entertainment gratification (PEG) and perceived application quality (PAQ) with the technology acceptance model (TAM). By arguing that behavioural intention (BI) does not automatically lead to actual use (AU), we investigated the moderating effect of facilitating conditions (FC) on the relationship between BI and AU. A quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…Therefore, intention to use can predict the appropriate behavior as long as the person takes action voluntarily ( Purwanto and Loisa, 2020 ). In the technology acceptance model, actual usage behavior is modeled as a direct function of behavioral intention ( Hossain et al, 2017 ). In addition, in the construction of the technology acceptance model developed by Davis (1989) , a person's intention to use technology is also determined by attitude.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Therefore, intention to use can predict the appropriate behavior as long as the person takes action voluntarily ( Purwanto and Loisa, 2020 ). In the technology acceptance model, actual usage behavior is modeled as a direct function of behavioral intention ( Hossain et al, 2017 ). In addition, in the construction of the technology acceptance model developed by Davis (1989) , a person's intention to use technology is also determined by attitude.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…This research assumes that facilitating conditions may help institutional investors by providing knowledge, resources, and help to make a decision on investment in Cambodia. Plenty of research has shown facilitating conditions to be significant to specific behaviors or reasons for investment [23,[40][41][42][43]. In the process of investment behavior, the lack of financial data infrastructure, fast internet connectivity, appropriate financial software or information systems, etc., could be a barrier to making proper investment behaviors.…”
Section: Facilitating Conditions and Investment Decisionmentioning
confidence: 99%
“…Language was found significant moderator in a website evaluation study (Alcántara-pilar, Barrio-garcía, & Rodríguez-lópez, 2018). Facilitation conditions was found significant moderator in a study on adoption of location based services (Hossain, Chan, & Ahmed, 2017). Gender and information technology capability was found significant moderator in a study on apps operating on shared economy concept (Y.…”
Section: Factors Relevant To Technology Based On Reviewmentioning
confidence: 99%
“…Personality traits, sense of humor, emotions and perceived necessity of ease of use can also have moderating effect on intention to access in-app advertisements (Lamey, Deleersnyder, Steenkamp, & Dekimpe, 2018;Shim et al, 2018;Yeh, Wang, Li, & Lin, 2017). Prior experience and facilitation conditions previously used in UTAUT model as moderating factor can be used to measuring consumer intention to access in-app ads (Hossain et al, 2017;Shi & Chow, 2015;Spreer & Kallweit, 2014). Information technology capability also referred as self-efficacy can have a moderating role in intention to access in-app ads.…”
Section: Moderators Relevant To In-app Advertisementmentioning
confidence: 99%